Akuntabilitas Otorita IKN Dalam Pengelolaan Anggaran Pembangunan Ibu Kota Nusantara Kajian Hukum Pemerintahan Terhadap Prinsip Good Governance - Ni Putu Intan Cahyani Putri; Hikam Huwlwanullah (Fakultas Hukum, Universitas Warmadewa, 2025)
The development of the Capital City of Nusantara (IKN) as a national strategic project raises accountability issues in budget management by the Capital City of Nusantara Authority (OIKN), mainly due to unclear authority, dual institutional status, and weak oversight mechanisms. This study's goal is to investigate the application of OIKN accountability in the budget management of IKN development based on the legal framework of governance and good governance principles, identify normative challenges that cause accountability gaps, and formulate legal policy recommendations to strengthen budget governance. Based on primary, secondary, and tertiary legal materials gathered through a literature review, this study employs a normative legal technique with a legislative, conceptual, and case approach. The results of the analysis show that the OIKN legal framework, particularly the IKN Law and its derivative regulations, contains ambiguities regarding the limits of authority and accountability mechanisms, thus that it is not entirely consistent with the tenets of legal certainty, transparency, and accountability. The main findings also reveal weak internal and external oversight, a lack of public transparency, and the risk of budget inefficiency and irregularities due to the flexibility of IKN's authority, which is not balanced by checks and balances mechanisms. This research advances our knowledge of the normative implications of IKN development, particularly the need for regulatory strengthening, independent audits, periodic transparency, and public participation. It is concluded that reformulating the legal framework and strengthening oversight instruments are prerequisites for ensuring the principles of accountability, transparency, and good governance in the development of the IKN. Further research could expand this study to include an empirical evaluation of the effectiveness of policy recommendation implementation.